Systemic cohesion in social media conversations: Cases on Facebook and Twitter - Muttaqien, Muhammad Zainal; Hardjanto, Tofan Dwi; Ma’ruf, Amir (Indonesian Journal of Applied Linguistics, 2019)
As a new way of communication, social media conversations on the Internet do have some characteristics that are different from common face-to-face conversations. One of the differences lies in the existence of systemic cohesion in addition to the established conventional cohesion. Systemic cohesion is a form of structural and textual unity which is generated by the system of a social media platform and is not available in offline discourse. This article is aimed at describing the phenomena of systemic cohesion of social media conversations, particularly on Facebook and Twitter, by analyzing them based on the classification of cohesive devices made by Halliday and Hasan (1976, 1985). In general, systemic cohesion can be distinguished into structural and textual cohesion. The former is represented by the functions of conversation components, indentation, and vertical line whereas the latter is implemented in the form of mention and hashtag. Facebook and Twitter share both similarities and differences in either case.